Geneflow 2000-2001 - International Plant Genetic Resources Institute (2001)
This is a publication that serves to contribute to the flow of information about the importance of the Earth's plant genetic resources. This issue features a special section on the role played by women in the conservation, management and use of plant genetic resources around the world